Um Estudo De Provas E Refutações De Imre Lakatos - Carvalho, Henrique Marins De [UNIFESP] (2018)
Proofs And Refutations Is One Of The Most Important Works Of The Hungarian Philosopher Imre Lakatos (1922-1974) And Its Main Topic Is The Progress Evaluation Of Mathematics. The Text Is Structured As A Ficcional Story Told With The Literary Resource Of A Dialogues Set Involving A Teacher And His Pupils Arguing About The Euler Theorem About Polyhedra, Its Proofs And Counterexamples. Our Research Focused In Lakatos Ideas About The Growth Of Mathematics In A Heuristic Perspective And Has Been Set Up In Three Parts. In The First One, Aimed To Present Brief Biographical Informations About The Author And Comments About The Singular Characteristics Of This Writings Of His, Joined With Details Of His Intellectual Instruction, Highlighting Historicism And Refutationism; In The Second One, We Sought To Present A Reconstruction Of The Original Work, Joined With Comments. Finally, Taking A Stand Somewhat Far From The Text, We Selected And Explored Substantial Philosophical Questions Concerning The Truth, The Heuristic As